2014
DOI: 10.11648/j.hss.20140202.11
|View full text |Cite
|
Sign up to set email alerts
|

Early Marriage in South Wollo and East Gojjam Zones of the Amhara Region, Ethiopia

Abstract: Early marriage has profound physical, intellectual, psychological and emotional impacts and reduces educational opportunities and the chance for personal growth for both boys and girls. This study investigated the prevalence of early marriage in South Wollo and East Gojjam zones of the Amhara Region in Ethiopia. Data were collected from 769 respondents (476 females and 293 males) who were randomly selected from two zones. Structured questionnaires, focus groups and in-depth interviews were used for data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 1 publication
2
17
3
Order By: Relevance
“…The current analysis indicated that uneducated girls were more likely to experience child marriage as compared to those relatively educated. This study was consistent with previous studies done in South Wollo and East Gojjam, Ethiopia [6], in Pakistan [8], in Indonesia [15], in Serbia [16], in Bangladesh (17,18) and Nepal (19). From these across findings we understood that educated girls have more freedom and are better able to exercise their rights than non-educated girls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current analysis indicated that uneducated girls were more likely to experience child marriage as compared to those relatively educated. This study was consistent with previous studies done in South Wollo and East Gojjam, Ethiopia [6], in Pakistan [8], in Indonesia [15], in Serbia [16], in Bangladesh (17,18) and Nepal (19). From these across findings we understood that educated girls have more freedom and are better able to exercise their rights than non-educated girls.…”
Section: Discussionsupporting
confidence: 92%
“…A few previous studies had been conducted on child marriage and its associated factors in Amhara region, Ethiopia. For instance, earlier studies conducted in Sinan District, South Wollo and East Gojjam Zones reports indicated that education, residence [6,13], media exposure [6] and wealth status [13] were associated factors of child marriage. However, these studies were small coverage area in Amhara region.…”
Section: Despite Majority Of Countries In the World Adopted Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice of early marriage is also common among Ethiopian women. The prevalence of early marriage among reproductive-age group women ranges from 26% in Addis Ababa to 87% in the eastern region of Amhara [ 3 , 10 , 11 ]. In addition, according to the reports from Ethiopian Demographic and Health Surveys (EDHS) 2005, 2011, and 2016, the prevalence of early marriage among women aged 20–24 years is 66%, 63%, and 58% respectively [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…have affected students' learning (Ashebir & Bereket [5] [21]). This means, the long-standing cultural misconception of the community and the family such as forced marriage, early marriage, abduction, verbal insult, beating up, insecurity and rape are disturbed students' schooling (UNESCO [22]; Guday, [23]; Jones, Bekele, Stephenson, Gupta, Pereznieto, Guday, Betlehem & Kiya [24], Kerebih & Mulunesh [25]; MoE [10]). Thus, low completion rate has more implication for girls than boys due to low median age of marriage for girls (16.5) than for boys (21.8).…”
Section: Introductionmentioning
confidence: 99%